Modeling of polymer matrix composites using VBO model and finite element method formulations - Acar, Alperen (My University, 2016)
Polymeric materials are widely used in industry and researched in academia due to their low weight and ease on processing. But the mechanical properties of polymers are mostly low, in a comparison to metallic materials. Because of low strength and stiffness the mechanical properties of polymers are needed to be enchanced by composing them with various kinds of reinforcements. On the other hand, graphene, is a wonder nano-material which has 130 GPa of ultimate strength and 1 TPa of elastisity modulus. This superior properties of graphene makes it a great candidate for a polymer reinforcing agent. But the relevant literture shows us that the technology of polymer matrix graphene nanocomposites has to be improved to exhibit the superior properties of this nano material. This work has three tresholds, first the production and characterization of graphene-epoxy nanocomposite, second, modeling the total viscoelastic - viscoplastic behavior of the nanocomposite and third part is to implement the proposed model to finite element method for possible future use of the model on structural analysis. In the composition processes with nanomaterials, the biggest drawback is agglomeration of the nanomaterials. In this work, this problem is tried to overcome using a solvent and a sonication procedure before mixing the nano material with the prepolymer (in this work, epoxy resin). The mechanical characterization of the produced material is done by performing tensile tests and DMA tests. The mechanical properties are enchanced with the addition of graphene. xiii In this work, Cooperative-VBO model which is developed for modeling temperature dependent mechanical behavior by ÇOLAK, AHZİ and REMOND is modified to represent the behavior of nanocomposites. For modeling the mechanical behavior of nanocomposites, two main modifications are done. First one is redefining stiffness-temperature model of Mahieux and Reifsdner using a two step Mori-Tanaka scheme. In this scheme, the well dispersed (effective) and agglomerated regions are taken as different phases. Therefore the agglomeration effect of graphene is taken into account. Storage modulus of pure epoxy and graphene-epoxy nanocomposites with different graphene fractions are modeled using the modified model. The model shows good agreement with the experimental results.Second modification is on viscoplastic part,in particular, two scalar material parameters of the plastic strain rate function, activation energy ΔHβ, and activation volume V are redefined as functions of graphene fraction using Tagayanagi averaging approach. For the post - yield behavior of the nanocomposites, two parameters of the previously used tangent modulus function, ET0 and α, are defined as functions of graphene fraction, numerically. Therefore, the total viscoelastic - viscoplastic behavior of graphene nanocomposite materials are defined. The proposed model is capable of modeling material behavior for different temperature and strain rates as well. Model results are compared to test results to test the accuracy, good match with the experimental data is observed. In the last part, a computational procedure is defined using forward gradient method, for finite elemnt method implementation. This part leads the further usage of the proposed model for strucural analysis for possible future applications using nanocomposite materials. This work contributes to the related literature with a unique constitutive equation for modeling of epoxy-graphene nanocomposites. As explained above, the proposed model is capable of modeling the total viscoelastic-viscoplastic, temperature dependent mechanical behavior of such nanocomposites for different graphene fractions. The prediction capabilities of the model is tested through a set of test data, and it is shown that the prediction capabilities of the model are very good. Another unique contribution to the related liteature is the developed computational scheme. With this addition, it is shown that the proposed model can be used for structural analysis on possible future applications.

Polimer malzemeler, hem ağırlık avantajları ve hem de imalat kolaylıkları sebebiyle endustriyel olarak ve akademik calışmalarda oldukca yaygın kullanılmaktadırlar. Fakat bu yaygın kullanıma karşın, mekanik ozellikleri metalik malzemelere kıyasla coğunlukla duşuk kalmaktadır. Dayanım bakımından karşılaşılan bu yetersizlik bizleri, polimer malzemeleri, ceşitli katkılarla zenginleştirip, dayanımını arttırmaya yoneltmektedir. Diğer yandan, Grafen, 130 GPa kopma mukavemeti ve 1 TPa civarında olculmuş elastisite modulu ile, polimerik malzemelerin dayanımını artırabilecek oldukca guclu bir takviye malzemesi adayı olmaktadır. Fakat ilgili literatur incelendiğinde, bu olağanustu ozelliklere sahip nano malzemenin teknolojisinin, hem endustriyel hem de akademik anlamda geliştirilmeye muhtac olduğu anlaşılmaktadır. Bu calışma, uc aşamadan oluşmaktadır. İlk olarak grafen - epoksi nanokompozit malzeme uretilmiş, gerekli gorulen mekanik ve morfolojik testlere tabii tutularak uretilen malzeme karakterize edilmiştir. İkinci olarak, malzemenin toplam viskoelastik - viskoplastik davranışını modellenmiş ve son olarak onerilen model icin bir hesaplamalı prosedur oluşturularak sonlu elemanlar yontemi implementasyonu gercekleştirilmiştir. Nano malzemerle hazırlanan kompozitlerde karşılaşılan en oneml problem, nano malzemenin topaklanma eğiliminden kaynaklanan, heterojen yapılar olmaktadır. Bu problemin ustesinden gelmek icin bu calışmada grafen oncelikle bir ultrasonik karıştırıcı kullanılarak bir solvent icinde cozdurulmuş, daha sonra epoksi recine ile karıştırılmıştır. Uretilen malzemenin mekanik karakterizasyonu cekme testleri ve DMA xv testleri ile gercekleştirilmiştir. Grafen katkısı ile mekanik ozelliklerin iyileştiği gozlenmiştir. Nano kompozitin toplam mekanik davranışını modellemek amacıyla, Colak, Ahzi ve Remond tarafında 2013 yılında geliştirilen Cooperative-VBO modeli modifiye edilmiştir. Model, gerinim hızı tensorunun eklemeli bir formunu kullanmaktadır. Bu sebeple, modelin viskoelastik ve viskoplastik kısımları ayrı ayrı ele alınmıştır. Grafen katkısının viskoelastik davranış uzerindeki etkisini modellemek icin iki adımlı bir Mori- Tanaka şeması kullanılmıştır. Bu yaklaşımla, grafenin etkin olarka cozunduğu ve topaklandığı bolgeler ayrı ayrı ele alınmış ve boylece topaklanmanın elastik davranış uzerindeki nonlineer etkisi modellenmiştir. Epoksi ve grafen takviyeli nanokompozit malzemenin DMA testinden elde edilen depolama modulu modifiye edilen model ile modellenmiştir. ve modelin deney sonucları ile uyumlu cevap verdiği gosterilmiştir. Viskoplastik kısımda ise, model icindeki iki skalar malzeme parametresi, aktivasyon enerjisi, ΔHβ, ve aktivasyon hacmi V, Tagayanagi ortalaması yaklaşımı ile grafen oranının fonksiyonu olarak tanımlanmıştır. Akma sonrasında gorulen non-lineer davranışın modellenmesi amacıyla da tanjant modulu denklemi icindeki iki parametre, ET0 ve α, grafen hacim oranının fonksiyonu şeklinde tanımlanarak tanjant modulu denklemi modifiye edilmiştir. Onerilen model, malzeme uzerindeki grafen katkısını, değişen sıcaklık ve deformasyon hızı ile beraber modelleyebilmektedir. Model cevapları, test sonucları ile karşılaştırılmış ve oldukca uyumlu oldukları gozlenmiştir. Son olarak, Forward gradient metodu kullanılarak, hesaplamalı bir prosedur oluşturulmuş, boylece onerilen modelin, sonlu elemanlar yontemi kullanılarak yapılacak yapısal analizlerde bunye denklemi olarak kullanılması mumkun kılınmıştır. Calışma, ilgili literature, epoxy nanokompozit malzemesi icin kullanılabilecek ozgun bir bunye denklemi kazandırmıştır. Onerilen modelin kestirme yetenekleri değişen grafen oranları icin test edilmiş ve oldukca uyumlu sonuclar verdiği gozlemlenmiştir. Calışmanın ilgili literature bir başka katkısı isei model icin onerilen hesaplamalı şemadır. Onerilen hesaplamalı cerceve, bunye denklemini, ileride ihtiyac duyulması muhtemel yapısal analiz uygulamalarında kullanılmasını mumkun kılmaktadır.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Keywords: Graphene; Nanocomposite; Constitutive equation; VBO; Grafen; Nanokompozit; Bunye denklemi; VBO